2013
DOI: 10.3402/gha.v6i0.19274
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol use in early and late adolescence among the Birth to Twenty cohort in Soweto, South Africa

Abstract: BackgroundAlcohol is a risk factor for the leading causes of mortality and morbidity among young people globally. Youth drinking, initiated in early adolescence and continued into early adulthood, is influenced by maternal socio-demographic factors and maternal education. Limited prospective data exists in South Africa on the prevalence of alcohol use during adolescence and adolescent and maternal socio-demographic correlates.ObjectiveTo examine the prevalence of lifetime alcohol use during early (13 years) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 26 publications
5
18
0
Order By: Relevance
“…The results of the study further indicated that adolescents from two-parent households reported lesser risk-taking behavior compared to other family structures. These findings are validated by the works of previous writers who documented that adolescents from such households reported a delay or reduction of engagement in sexual activity ( 38 ); reduced levels of self-harm compared to those from the stepparent, single-parented or no-parent groups ( 19 ) and receive higher levels of parental closeness and monitoring, dimensions of a family structure which act as a buffer against the adoption of risk-taking behavior adolescents ( 39 ). Moreover, emerging data suggest that during childhood and adolescence, close family relationships can ameliorate the impact that adversity has on lifespan physical and mental health ( 30 ).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The results of the study further indicated that adolescents from two-parent households reported lesser risk-taking behavior compared to other family structures. These findings are validated by the works of previous writers who documented that adolescents from such households reported a delay or reduction of engagement in sexual activity ( 38 ); reduced levels of self-harm compared to those from the stepparent, single-parented or no-parent groups ( 19 ) and receive higher levels of parental closeness and monitoring, dimensions of a family structure which act as a buffer against the adoption of risk-taking behavior adolescents ( 39 ). Moreover, emerging data suggest that during childhood and adolescence, close family relationships can ameliorate the impact that adversity has on lifespan physical and mental health ( 30 ).…”
Section: Discussionsupporting
confidence: 70%
“…Alcohol and other drugs (AOD) use among adolescents remains one of this age cohort prominent risk-taking behavior which has been associated with social issues like crime, including sexual and grievous bodily harm, assaults and murder ( 17 ), gang activities, vandalism, bullying, and truancy within school premises ( 18 ). Additionally, alcohol is alleged to increases the risk of engagement in sexual risk behavior, leading to sexually transmitted infections (STIs) ( 19 ) and unplanned pregnancy which in most cases lead to unsafe abortions which are the leading cause of death for women aged 15–19 worldwide ( 20 ). There is also a link between substance use and self-harm behavior in adolescents with female adolescents being three times more likely and male adolescents being 17 times more likely to attempt self-harm while under the influence of alcohol ( 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…As described in the South African National Drug Master plan 2013–2017 (Central Drug Authority, ), this can be addressed through the involvement of local government, primary healthcare providers, maternity healthcare, community leaders and youth within the communities. Research has shown that the younger the age of onset of alcohol consumption, the more likely it is that the person will experience alcohol problems later in life (Hingson & Zha, ; Ramsoomar, Morojele, & Norris, ). With regard to gender‐specific interventions, there are several reasons why health professionals should reach women when planning prevention, treatment and care.…”
Section: Resultsmentioning
confidence: 99%
“…In rural South Africa, the prevalence of alcoholism is 22% among school adolescents [12]. In this country, consumption mainly concerns the high teens, male, school late, but there is no impact of social status [13]. Also, parental influence is revealed as an important determinant [14].…”
Section: Excessive Alcohol Intakementioning
confidence: 99%